Anti-Acanthamoeba Activity of Brominated Sesquiterpenes from Laurencia johnstonii - Sara García-Davis; Ines Sifaoui; María Reyes-Batlle; Ezequiel Viveros-Valdez; José E. Piñero; Jacob Lorenzo-Morales; José J. Fernández; Ana R. Díaz-Marrero (Marine Drugs, 2018)
Focused on our interest to develop novel antiparasistic agents, the present study was aimed to evaluate the biological activity of an extract of Laurencia johnstonii collected in Baja California Sur, Mexico, against an Acantamoeba castellanii Neff strain. Bioassay-guided fractionation allowed us to identify the amoebicidal diastereoisomers α-bromocuparane (4) and α-isobromocuparane (5). Furthermore, bromination of the inactive laurinterol (1) and isolaurinterol (2) yielded four halogenated derivatives, (6)⁻(9), which improved the activity of the natural sesquiterpenes. Among them, the most active compound was 3α-bromojohnstane (7), a sesquiterpene derivative which possesses a novel carbon skeleton johnstane.